Jaina Traces at Eswarankod in Palakkad, Kerala - K . Rajan
Identification of Jaina images in one of the strongholds of Jainism in Kerala – Eswaramkod— has not been so easy. Scholars who wrote on the two images spoke of them merely as representative of the concept of Tirthankara rather than being any of the particular Tirthankaras of Jaina pantheon. Although, historians have accepted the fact that the Eswarankod images take us back to an early medieval past, it was not possible for them to say much about the identity of the images merely because much less effort has been made to compare them with some other models found elsewhere. Also, there were fewer efforts to look into the iconographic aspects of the Jaina images found in the state. This has resulted in historians following some observations made by established authorities. Archaeological investigations lead to some accidental discoveries which again throw light upon a hidden past. Three years ago, the present author could find three front‐facing lion figures on the pedestal of one of the images and establish it clearly as that of Mahavira Tirthankara. A detailed documentation of the two images and the Associated aspects of early medieval Jaina iconography reflected in them was made subsequently. Still, much is left to be taken up by subsequent scholars.